The correlation between tic disorders and allergic conditions in children: A systematic review and meta-analysis of observational studies - Ying Chang; Ying Zhang; Yifan Bai; Run Lin; Yaping Qi; Min Li; Min Li (Frontiers Media S.A., 2023)
AimTo evaluate the correlation between tic disorders and allergies and to inform strategies for the treatment and prevention of tic disorders.MethodsWe conducted online searches of the MEDLINE, Embase, Cochrane, CNKI, CBM, WanFang, and VIP Information databases. Case-control studies and cohort studies related to tic disorders and allergic conditions were searched. Two researchers screened the literature, extracted data, and evaluated quality in strict accordance with the predetermined retrieval strategy and inclusion criteria. Finally, RevMan 5.4 software was used to conduct a meta-analysis. We used the Grading of Recommendations, Assessment, Development, and Evaluations (GRADE) approach to rating the certainty of evidence about each allergy outcome as high, moderate, low, or very low.ResultsWe obtained seven eligible studies involving eight allergic conditions. The following allergic conditions were significantly associated with the presence of a tic disorder: asthma (OR = 1.90, 95% CI = 1.57-2.30, P < 0.001), allergic rhinitis (OR = 2.61, 95% CI = 1.90-3.57, P < 0.001), allergic conjunctivitis (OR = 3.65, 95% CI = 1.53-8,67, P = 0.003), eczema (OR = 3.87, 95% CI = 2.24-6.67, P < 0.001) and food allergy (OR = 2.79, 95% CI = 1.56-4.99, P < 0.001). There was no significant correlation between atopic dermatitis, urticaria, drug allergy, and tic disorder.ConclusionThe occurrence of tic disorders may be associated with the presence of certain allergic disorders. However, whether allergy is one of the causes of tic disorders remains unclear.Systematic review registrationThe registration number for this systematic review is PROSPERO: CRD42021231658.